1992
DOI: 10.1037/0022-3514.62.4.634
|View full text |Cite
|
Sign up to set email alerts
|

Job experiences over time, multiple roles, and women's mental health: A longitudinal study.

Abstract: Are changes over time in the quality of a woman's job associated with changes in her psychological distress? Do family roles moderate these relationships? We addressed these questions using longitudinal data from a 2-year 3-wave study of a stratified random sample of 403 employed women who varied in occupation, race, partnership, and parental status. After estimating individual rates of change for each woman on each of the predictors and the outcome, we modeled the relationships between family role occupancy a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
81
0
1

Year Published

1994
1994
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 51 publications
4
81
0
1
Order By: Relevance
“…Although distinguishable, these are not independent domains}for instance, parenting stress is connected to marital discord. Stress in parenting is more strongly tied to parenting behaviour and children's developmental outcomes than is stress in most other domains}arguably because parenting stress is most proximal to the processes that contribute to the development of children's problem behaviours (Barnett et al, 1992;Creasey and Reese, 1996). Far from being rare or limited only to severe family problems, mildly stressful experiences in parenthood are common, and their effects accumulate over time (Crnic and Low, 2002).…”
Section: Parenting Stress As a 'Relationship' Process: Parent And Chimentioning
confidence: 96%
“…Although distinguishable, these are not independent domains}for instance, parenting stress is connected to marital discord. Stress in parenting is more strongly tied to parenting behaviour and children's developmental outcomes than is stress in most other domains}arguably because parenting stress is most proximal to the processes that contribute to the development of children's problem behaviours (Barnett et al, 1992;Creasey and Reese, 1996). Far from being rare or limited only to severe family problems, mildly stressful experiences in parenthood are common, and their effects accumulate over time (Crnic and Low, 2002).…”
Section: Parenting Stress As a 'Relationship' Process: Parent And Chimentioning
confidence: 96%
“…Participants who were able to balance family and work found that it was very helpful in maintaining their health (Hibbard & Pope, 1991;Lahelma, Arber, Kivel, & Roos, 2002), enhanced feelings of happiness (Baruch & Barnett, 1986), pro-moted women's self-esteem (Pietromonaco, Manis, & Frohardt-Lane, 1986;Reitzes & Mutran, 1994), allowed women to feel easily satisfied with their work and life (Adams, King, & King, 1996;Schoon, Hansson, & Salmela-Aro, 2005), and helped them discover that their family role could buffer stress that was related to their jobs (Barnett, Marshall, & Singer, 1992). In addition, Gottman (1999) found that a harmonious relationship was an important foundation in a successful marriage.…”
Section: Career Adjustmentmentioning
confidence: 97%
“…Cinamon & Rich, 2002;Schwarzberg & Dytell, 1996). On the other hand, women's well-being has been thought to be primarily affected by factors in the family domain and, furthermore, stressors from this domain have been thought to be able to have an especially negative effect on women (Barnett, Marshall, & Singer, 1992;Schwarzberg & Dytell, 1996).…”
Section: The Male Breadwinner Modelmentioning
confidence: 99%